2020
DOI: 10.1158/2326-6066.cir-20-0061
|View full text |Cite
|
Sign up to set email alerts
|

A DNA-Launched Nanoparticle Vaccine Elicits CD8+ T-cell Immunity to Promote In Vivo Tumor Control

Abstract: Cytolytic T cells (CTL) play a pivotal role in surveillance against tumors. Induction of CTL responses by vaccination may be challenging, as it requires direct transduction of target cells or special adjuvants to promote cross-presentation. Here, we observed induction of robust CTL responses through electroporation-facilitated, DNA-launched nanoparticle vaccination (DLnano-vaccines). Electroporation was observed to mediate transient tissue apoptosis and macrophage infiltration, which were deemed essential to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…The increased infiltration of antigen-presenting cells (APCs) is associated with an increased CD8 + T cell response. 27 In conclusion, we have shown the feasibility of targeting up to 40 neoantigens using a simple combination system. Multiple neoantigens were immunogenic in this approach, and the magnitude or type of immune response was independent of the size of the construct and the position of individual epitope within the vaccine.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The increased infiltration of antigen-presenting cells (APCs) is associated with an increased CD8 + T cell response. 27 In conclusion, we have shown the feasibility of targeting up to 40 neoantigens using a simple combination system. Multiple neoantigens were immunogenic in this approach, and the magnitude or type of immune response was independent of the size of the construct and the position of individual epitope within the vaccine.…”
Section: Discussionmentioning
confidence: 76%
“…The increased infiltration of antigen-presenting cells (APCs) is associated with an increased CD8 + T cell response. 27 …”
Section: Discussionmentioning
confidence: 99%
“…While both protein and DNA vaccination induced trimer-specific binding antibodies, DNA but not protein vaccination induced CD4 + and CD8 + T-cell responses as well as nAb responses. Differences in the mechanisms with which antigens traffic and present for protein versus DNA-encoded immunogens may underlie differential induction of immune phenotypes by these two routes of vaccination 56 . Protein antigens are supplied as a depot of soluble antigens and may rely on bulk flow in the lymphatic system for antigen trafficking 57 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have shown that epitope-based vaccines can effectively elicit protective immune responses against various pathogens, such as HIV and influenza viruses ( Oyarzún and Kobe, 2016 ; Ben-Yedidia and Arnon, 2007 ). Delivery of epitopes as DNA vaccines ( Wilson et al, 2003 ) or DNA-launched nanoparticle vaccines ( Xu et al, 2020 ) are known to induce strong CTL responses.…”
Section: Introductionmentioning
confidence: 99%